PENGARUH KOMBINASI JENIS CENDAWAN ENTOMOPATOGEN DAN FREKUENSI APLIKASI TERHADAP MORTALITAS KUTU KEBUL (BEMISIA TABACI) - FITRAH J, MULYA Fitrah; Prayogo, Yusmani (LenteraBio: Berkala Ilmiah Biologi, 2013)
One obstacle in current increased soybean production is impaired whitefly infestation. Economically, whitefly infestation can reduce yields by 40-80% if no control measures. Previous study showed that the Beauveria bassiana fungus was able to kill whitefly infestation, but the mortality of whitefly infestation only 50% by using a density of 108/ml conidia. This study aimed to improve mortality whitefly infestation on soybean plants using three different types of fungi and frequency of application. This study was an experimental study using a randomized block design (RBD) with two treatment factors are the type of fungus (Lecanicillium lecanii, Metarizhium anisopliae and Beauveria bassiana) and the frequency of application (1 time/week,    2 times/week, 3 times/week and 4 times/week) with three repetitions. The data obtained were analyzed by using two-way program MSTATC. The conclusion of this study were a combination of types of fungi with the frequency of applications that effectively kills fleas whitefly is a type of fungus L. lecani with frequency application 3 times/week.